Callous-unemotional traits and moral disengagement as antecedents to the peer influence effect: moderation or mediation? - Walters, Glenn D. (Journal of crime and justice, 2018)
The purpose of this study was to determine whether callous-unemotional (CU) traits and moral disengagement (MD) serve as antecedents to the peer influence effect. There were two hypotheses tested in this study: (1) Moral disengagement will moderate the effect of CU traits on peer influence, and (2) Moral disengagement will mediate the effect of CU traits on peer influence. These two hypotheses were tested in a sample of 1354 male and female delinquents from the Pathways to Desistance study, using four waves of data, with six months between waves. Contrary to Hypothesis 1, regression and path analyses failed to support a moderating effect for moral disengagement with respect to the CU → peer influence or CU → peer/participant delinquency relationships. Consistent with Hypothesis 2, however, path analysis revealed that moral disengagement successfully mediated the CU → peer influence relationship. In further support of Hypothesis 2, a control pathway running from CU to moral disengagement to peer selection failed to achieve significance. These results suggest that the effect of CU traits on delinquency may be mediated by variables like moral disengagement and peer delinquency, a position consistent with the moral model of criminal lifestyle development.